Steer-by-switch system design for vehicles - Safarzadeh, Daryoush; Sulaiman, Shamsuddin; Abdul Aziz, Faieza; Ahmad, Desa; Majzoobi, Gholam Hossein (Academic Journals, 2011)
In this paper, design of a steer-by-switch system as a new technology to steer vehicles devoid of a steering wheel was described. In this method, steering of the vehicle was achieved by two push button switches which were related to the front wheels via an electro-hydro-mechanical system. The objective of this design was to eliminate the prejudicial effects associated with the utilisation of steering wheels in machines. Furthermore, this system provided a flexible and comfortable steering for drivers of heavy duty machinery and off-road vehicles as well as the feasibility of driving for invalid persons who were feeble in one hand. Modeling of the system was achieved to compare its characteristics with two common types of steering systems. To enhance the reliability of the system, an auxiliary steering system served as a safeguard against the failure of the main steering system.